Constraining the Contribution of Hydrothermal Iron to Southern Ocean Export Production Using Deep Ocean Iron Observations - Tagliabue, Alessandro; Bowie, Andrew R.; Holmes, Thomas; Latour, Pauline; van der Merwe, Pier; Gault-Ringold, Melanie; Wuttig, Kathrin; Resing, Joseph A. (Frontiers in Marine Science, 2022)
Hydrothermal iron supply contributes to the Southern Ocean carbon cycle via the regulation of regional export production. However, as hydrothermal iron input estimates are coupled to helium, which are uncertain depending on whether helium inputs are based on ridge spreading rates or inverse modelling, questions remain regarding the magnitude of the export production impacts. A particular challenge is the limited observations of dissolved iron (dFe) supply from the abyssal Southern Ocean ridge system to directly assess different hydrothermal iron supply scenarios. We combine ocean biogeochemical modelling with new observations of dFe from the abyssal Southern Ocean to assess the impact of hydrothermal iron supply estimated from either ridge spreading rate or inverse helium modelling on Southern Ocean export production. The hydrothermal contribution to dFe in the upper 250 m reduces 4–5 fold when supply is based on inverse modelling, relative to those based on spreading rate, translating into a 36–73% reduction in the impact of hydrothermal iron on export production. However, only the spreading rate input scheme reproduces observed dFe anomalies >1 nM around the circum-Antarctic ridge. The model correlation with observations drops 3 fold under the inverse modelling input scheme. The best dFe scenario has a residence time for hydrothermal iron that is between 21 and 34 years, highlighting the importance of rapid physical mixing to surface waters. Overall, because of its short residence time, hydrothermal Fe supplied locally by circum-Antarctic ridges is most important to the Southern Ocean carbon cycle and our results highlight decoupling between hydrothermal iron and helium supply.